2016
DOI: 10.1186/s12864-016-3115-2
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals dynamic changes in A-to-I RNA editome during early human embryogenesis

Abstract: Background: A-to-I RNA-editing mediated by ADAR (adenosine deaminase acting on RNA) enzymes that converts adenosine to inosine in RNA sequence can generate mutations and alter gene regulation in metazoans. Previous studies have shown that A-to-I RNA-editing plays vital roles in mouse embryogenesis. However, the RNA-editing activities in early human embryonic development have not been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
(42 reference statements)
7
25
1
Order By: Relevance
“…RNA‐sequencing provides an unprecedented opportunity to identify RNA editing sites in yeast, fungi , humans, and plants (Bruno et al ., ; Peng et al ., ; Bentolila et al ., ; Eifler et al ., ; Qiu et al ., ). We identified 692 RNA editing sites in the mitochondrial genome of G. hirsutum , based on analysis of RNA‐seq datasets.…”
Section: Discussionmentioning
confidence: 97%
“…RNA‐sequencing provides an unprecedented opportunity to identify RNA editing sites in yeast, fungi , humans, and plants (Bruno et al ., ; Peng et al ., ; Bentolila et al ., ; Eifler et al ., ; Qiu et al ., ). We identified 692 RNA editing sites in the mitochondrial genome of G. hirsutum , based on analysis of RNA‐seq datasets.…”
Section: Discussionmentioning
confidence: 97%
“…Here, three transcript isoforms with TPM = 0 in 21 cells were dropped, and expression profiles of 6 transcript isoforms were analyzed (Figure 7B). Qiu et al (2016) constructed A-to-I RNA editome during early human embryogenesis and demonstrated Adar expression and A-to-I RNA editing level remained relatively stable until 4-cell stage, but dramatically decreased at 8-cell stage, continually decreased at morula stage. Similar to human embryogenesis, in mouse embryogenesis, we demonstrated Adar expression level was stable and remarkably elevated until 2-cell stage, but sharply decreased at 4-cell stage, continually decreased until blastocysts stage.…”
Section: The Identification Of Iss In Consecutive Stages Of Preimplanmentioning
confidence: 99%
“…Enzymes triggering RNA editing are essential for several processes requiring cell growth and adaptation (e.g., embryogenesis, proliferation, immunity and neural plasticity) [27][28][29]. In this respect, activity of editing enzymes can lead to various functional cellular outcomes depending on the RNA molecules being modified and of the type of modification.…”
Section: Editing Of Mirnamentioning
confidence: 99%
“…In early stages of human embryogenesis (eight cells to the morula stage), RNA editing activity was reported to be low [27], but whether this observation can be extrapolated to miRNA editing is unknown. Nevertheless, in murine E15 embryonic stage miRNA editing events were reported to be rare, but to increase with postnatal development [122].…”
Section: Developmentmentioning
confidence: 99%